Mastery Imagery Ability Is Associated With Positive Anxiety and Performance During Psychological Stress - Williams, Sarah E.; Quinton, Mary L.; Veldhuijzen van Zanten, Jet J. C. S.; Davies, Jack; Möller, Clara; Trotman, Gavin P.; Ginty, Annie T. (Frontiers in Psychology, 2021)
Mastery imagery (i.e., images of being in control and coping in difficult situations) is used to regulate anxiety. The ability to image this content is associated with trait confidence and anxiety, but research examining mastery imagery ability’s association with confidence and anxiety in response to a stressful event is scant. The present study examined whether trait mastery imagery ability mediated the relationship between confidence and anxiety, and the subsequent associations on performance in response to an acute psychological stress. Participants (N = 130; 55% male; Mage = 19.94 years; SD = 1.07 years) completed assessments of mastery imagery ability and engaged in a standardized acute psychological stress task. Immediately prior to the task, confidence, cognitive and somatic anxiety intensity, and interpretation of anxiety symptoms regarding the task were assessed. Path analyses supported a model whereby mastery imagery ability mediated the relationship between confidence and cognitive and somatic anxiety interpretation. Greater mastery imagery ability and confidence were both directly associated with better performance on the stress task. Mastery imagery ability may help individuals experience more facilitative anxiety and perform better during stressful tasks. Improving mastery imagery ability by enhancing self-confidence may help individuals successfully cope with anxiety elicited during stressful situations.